Switching, dual spin-filtering effects, and negative differential resistance in a carbon-based molecular device - Sun, Changqing (2013)
We present ab initio calculations for spin-dependent electron transport in a molecular device constructed by two carbon chains capped with a phenyl ring, which is sandwiched between two zig-zag-edged graphene nanoribbon (ZGNR) electrodes, where the ZGNRs are modulated by external magnetic field. The coexistence of switching, dual spin-filtering effects, and negative differential resistance (NDR) in the model device is demonstrated with the theory of carbon π-electrons. Interestingly, a two-state molecular conformational switch can be realized by changing the orientation between the planes of phenyl ring and electrodes, where the majority-spin current modulation (ON/OFF ratio) is 170–479 within the considered bias window. Moreover, the device shows perfect dual spin-filtering effect and can generate and control a full dual spin-polarized current through either the source-drain voltage or magnetic configuration of the electrodes. The selective spin current is due to a dual selection rule, the symmetry match between two ZGNR electrodes spin channel, and the carbon chain’s spin selection in our system. In addition, the obvious NDR behavior has also been observed in our model.